Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

The dense indumentum with its polyphenol content may replace the protective role of the epidermis in some young xeromorphic leaves - Karabourniotis, George; Fasseas, Costas (Canadian Journal of Botany, 1996)
The bright, yellow-green, ammonia-induced fluorescence of polyphenol compounds contained in the nonglandular hairs and within the epidermis of Olea europaea and Quercus ilex leaves was age dependent. Epifluorescence microscopic examination of transverse sections of leaves from both species showed that abaxial and adaxial epidermal layers emitted the characteristic green-yellow bright fluorescence only in late developmental stages, when a considerable decrease of the trichome density had already occurred. At earlier developmental stages, only the dense and thick trichome layer emitted the bright green-yellow fluorescence. In addition, the trichomes of young leaves of Olea and Quercus resembled the glandular ones of other species morphologically and possibly functionally. These findings suggest that the protective role of the trichome against ultraviolet-B radiation damage and (or) other environmental factors is particularly significant during the early stages of leaf development and may be less important at later stages, when the protective role is taken over by the epidermis. Keywords: leaf hairs, phenolics, UV-B radiation damage, leaf development, Olea europaea L., Quercus ilex L.
doi: 10.1139/b96-043doi: 10.1139/b96-043The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: leaf development; leaf hairs; Olea europaea L.; phenolics; Quercus ilex L.; UV-B radiation damage